Circulating filarial antigen detection in brugian filariasis - TRIPATHI, PRAVEEN KUMAR; MAHAJAN, RAMESH CHANDER; MALLA, NANCY; MEWARA, ABHISHEK; BHATTACHARYA, SHAILJA MISRA; SHENOY, RANGANATHA KRISHNA; SEHGAL, RAKESH (Parasitology, 2016)
Human lymphatic filariasis (LF) is a major cause of disability globally. The success of global elimination programmes for LF depends upon effectiveness of tools for diagnosis and treatment. In this study on stage-specific antigen detection in brugian filariasis, L3, adult worm (AW) and microfilarial antigenaemia were detected in around 90–95% of microfilariae carriers (MF group), 50–70% of adenolymphangitis (ADL) patients, 10–25% of chronic pathology (CP) patients and 10–15% of endemic normal (EN) controls. The sensitivity of the circulating filarial antigen (CFA) detection in serum samples from MF group was up to 95%. In sera from ADL patients, unexpectedly, less antigen reactivity was observed. In CP group all the CFA positive individuals were from CP grade I and II only and none from grade III or IV, suggesting that with chronicity the AWs lose fecundity and start to disintegrate and die. Amongst EN subject, 10–15% had CFA indicating that few of them harbour filarial AWs, thus they might not be truly immune as has been conventionally believed. The specificity for antigen detection was 100% when tested with sera from various other protozoan and non-filarial helminthic infections.